Integrating climate change and habitat fragmentation to identify candidate seed sources for ecological restoration. Issue 4 (16th January 2017) - Harrison, Peter A.; Vaillancourt, René E.; Harris, Rebecca M. B.; Potts, Brad M.
Abstract: Anthropogenic change (climate change and habitat fragmentation) is driving a growing view that local seed collections may need to be supplemented with nonlocal seed as a strategy to bolster genetic diversity and thus increase evolutionary potential of plantings. While this strategy is becoming widely promoted, empirical support is limited, and there is a lack of accessible research tools to assist in its experimental testing. We therefore provide the Provenancing Using Climate Analogues (PUCA) framework that integrates the principles of the climate‐adjusted provenancing strategy with concepts from population genetics (i.e. potential inbreeding in small fragmented populations) as both a research and operational‐ready tool to guide the collection of nonlocal seed. We demonstrate the application of PUCA using the Midlands of Tasmania, Australia, a region that is currently undergoing large‐scale ecological restoration. We highlight multiple nonlocal seed sources for testing by identifying actual species distribution records that currently occupy environments similar to that projected to occur at the restoration site in the future. We discuss the assumptions of PUCA and the ecological considerations that need to be tested when moving nonlocal genotypes across the landscape.